COVID-19 in nursing homes: What syndromic and virological surveillance revealed about the first two epidemic waves - Philippe Gaspard; Martin Martinot (Journal of Infection Prevention, 2026)
Background Nursing homes were affected by COVID-19, and limited testing capacity during the first wave highlighted the value of complementary surveillance approaches. Objective To characterize clinical presentations, virological findings, and mortality identified through syndromic and virological surveillance during two COVID-19 waves. Materials and methods A retrospective study was conducted in 16 nursing homes in Northeastern France, including 1,493 residents monitored from February 2020 to February 2021. Residents were classified into four clinical sign patterns: combined general and respiratory signs (G and R), R only, G only, and asymptomatic positive SARS-CoV-2 tests (T+ only). Outbreaks were defined by at least three residents presenting G and R or T+ only within four consecutive days. Wave 2 analyses were conducted separately before and during immunization. Results Outbreak frequency and duration remained high during both epidemic waves, although smaller facilities were less likely to experience outbreaks. The proportion of residents presenting G and R declined from 62.9% during wave 1 to 53.0% and 38.9% during the pre-immunization and immunization periods, respectively ( p < 0.001), whereas G only presentations increased. Virological testing coverage among CSPs increased from 41.0% to 84.8% and 79.2%, respectively. Estimated 8-week mortality decreased from 25.4% to 20.5% and 12.8% ( p = 0.002). In multivariable analysis, clinical sign patterns (highest risk among G and R), older age, male sex, and not being tested were independently associated with mortality, while epidemic period was not. Discussion These findings highlight the complementary value of syndromic and virological surveillance for characterizing COVID-19 outbreaks in nursing homes.